Clinical Outcomes Following the Implementation of a Novel One-Year Training Program in Emergency Medicine in Karachi, Pakistan - Syed Ghazanfar Saleem; Saima Ali; Adeel Khatri; Sama Mukhtar; Wasfa Farooq; Quratulain Maroof; Muhammad Imran Jamal; Tariq Aziz; Kaniz Farwa Haider; Farah Z. Dadabhoy; Megan M. Rybarczyk (Ubiquity Press, 2023)
Background: Most Emergency Departments (EDs) in low- and middle-income countries (LMICs), particularly in Pakistan, are staffed by physicians not formally trained in Emergency Medicine (EM). As of January 2022, there were only 13 residency training programs in EM throughout all of Pakistan. Therefore, an intermediate solution-a one-year training program in EM-was developed to build capacity. Objective: To determine the impact of a novel training program in EM on clinical metrics and outcomes. Methods: The first cohort of a novel, one-year training program-the Certification Program in Emergency Medicine (CPEM)-completed the program in June 2019. The program consisted of two arms: CPEM-Clinical (CPEM-C), which included physicians from the Indus Hospital and Health Network (IHHN) ED; and CPEM-Didactic (CPEM-D), which included physicians from EDs across Karachi. Both groups participated in weekly conferences, such as didactics, small group discussions, workshops, and journal clubs. CPEM-C learners also received clinical mentorship from local and international faculty. Mortality, length of stay (LOS), and time-to-evaluation, as well as metrics in four key areas-patients at risk for cardiovascular disease/acute coronary syndrome, sepsis, respiratory illness, and intra-abdominal trauma-were assessed before and after the initial cohort at IHHN and compared with other groups in IHHN. Findings and Conclusions: More than 125,000 patients were seen from July to December 2017 (pre-CPEM) and July to December 2019 (post-CPEM). Overall, there were significant improvements in all clinical metrics and outcomes, with the exception of LOS and time-to-evaluation, and a trend toward improved mortality. In comparing CPEM graduates to other groups in IHHN ED, most metrics and outcomes significantly improved or trended toward improvement, including mortality. Implementation of a medium-duration, intensive EM training program can help improve patient care and the development of EM as a new specialty in lower-resource settings.